Isoflavone genistein as bone resorption inhibitor and bone formation stimulant an experimental study on guinea pig - Gener, Rosa Maria Wilhelmina DL.
The present study examined the effect of an isoflavone, genistein, on the degree and rate of experimental tooth movement in guinea pigs. Twenty nine adult guinea pigs were randomly assigned into one of the four groups (Male+Placebo, Male+Genistein, Female+Placebo, Female+Genistein). Each group received subcutaneous injection of their corresponding substance for 21 days, starting on the day the orthodontic appliance was installed. Direct linear measurements of tooth separation were documented daily. After the treatment period, one guinea pig from each group was euthanized for histologic study of the periodontium surrounding maxillary incisors. Comparing the mean degree of tooth separation showed a significant difference between the four groups (FEMALE+P7.089 mm; MALE+P6.731 mm; MALE+GEN 5.514 mm; FEMALE+GEN 4.56 mm), starting on Day 2 of appliance installation (P=0.031). A highly significant difference was found between the mean rate of both movement among the four groups starting on Day 4 (P=0.008) until the last day of the experiment, Day 21 (P=0.000) with the FEMALE+P group exhibiting the greatest rate (0.338 mm/day); followed by MALE+P (0.321 mm/day); MALE+GEN (0.263 mm/day); and FEMALE+GEN (0.217 mm/day). Total osteoclast count on the compression sides of both incisors also revealed significant differences among the four specimens (P=0.000), with FEMALE+P exhibiting the greatest number of osteoclasts, followed by MALE+P, MALE+GEN, and FEMALE+GEN; while total osteoblast count on the tension sides of both incisors also revealed significant differences among the four specimens (P=0.000), with FEMALE+GEN exhibiting the greatest number of osteoblasts, followed by FEMALE+P, MALE+GEN, and MALE+P. Results of this study suggest that genistein could decrease the degree and rate of tooth movement in guinea pigs.
Thesis (Master of Science in Dentistry)-- University of the Philippines Manila.
Keywords: Orthodontics; Tooth Movement; Isoflavone genistein